Genotype-Environmental (G x E) Interaction for Body Weights for Kuchi Chicken Ecotype of Tanzania Reared On-Station and On-Farm - Lwelamira , J. (International Journal of Poultry Science, 2012)
This study was carried out with the aim of determining magnitude of G x E interaction for body weights for Kuchi chicken ecotype of Tanzania reared under intensive (on-station) and extensive (free-range) management systems. Body weight was assessed at 8 (Bwt8), 12 (Bwt12), 16 (Bwt16) and 20 (Bwt20) weeks of age. Results for this study indicated average performance in all body weight measurements was significantly higher under intensive management compared to extensive management (p